2003
DOI: 10.1046/j.1524-475x.2003.11108.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells modulate the inflammatory but not the proliferative response in healing wounds

Abstract: Upon stimulation, mast cells release a heterogeneous group of factors that promote inflammation and influence cell proliferation. Mast cells accumulate at sites of injury, further suggesting a critical role in wound healing. To assess the importance of mast cells in tissue repair, we compared wound healing in mast cell-deficient WBB6F1/J-KitW/KitW-v (KitW/KitW-v) and wild type WBB6F1/++ (WT) mice. During the inflammatory phase, neutrophil infiltration into wounds of the KitW/KitW-v mice was significantly less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
122
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 46 publications
8
122
0
8
Order By: Relevance
“…However, these studies were performed with Kit W /Kit Wv mice, known to have additional abnormalities in the immune system (3,34). In particular, they are neutropenic (35), which may explain the observed reduction in neutrophil infiltration upon wounding (4,7). Although the impaired healing of Kit W / Kit Wv mice was rescued by reconstitution of the mice with mast cells (7), this finding does not provide a final proof for a role of mast cells in wound healing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these studies were performed with Kit W /Kit Wv mice, known to have additional abnormalities in the immune system (3,34). In particular, they are neutropenic (35), which may explain the observed reduction in neutrophil infiltration upon wounding (4,7). Although the impaired healing of Kit W / Kit Wv mice was rescued by reconstitution of the mice with mast cells (7), this finding does not provide a final proof for a role of mast cells in wound healing.…”
Section: Discussionmentioning
confidence: 98%
“…Experiments with mast cell-deficient Kit W /Kit Wv mice, which have mutations in the gene encoding the receptor tyrosine kinase Kit (3), gave inconsistent results. One study showed reduced neutrophil infiltration after wounding in these mice, whereas new tissue formation, including reepithelialization, angiogenesis, and collagen synthesis, was not affected (4). Two other studies confirmed that wound closure was not affected by loss of mast cells (5,6), whereas alterations in collagen remodeling were observed (5).…”
Section: Ast Cells Are Tissue-resident Cells and Well Known For Thementioning
confidence: 94%
“…Using these mice, studies have shown that mast cells are especially important for the infiltration of neutrophils into the wound. 27,28 Mast cells also produce many cytokines and growth factors that affect keratinocyte and endothelial cell function, which is important during the proliferative phase of healing. Mast cells generate epidermal growth factor, keratinocyte growth factor, and other mediators known to stimulate keratinocytes.…”
Section: Mast Cell Biologymentioning
confidence: 99%
“…Neutrophil knockdown experiments in mice result in repair that is even more rapid than in wild-type healing as long as conditions are sterile, indicating that these cells release signals that are inhibitory to some aspect of the repair process (Dovi et al, 2003). Mice null for Kit W (Kit -Mouse Genome Informatics) are deficient in Mast cells and show reduced numbers of neutrophils at a wound site, but otherwise normal repair (Egozi et al, 2003), whereas the PU.1 (Sfpi1 -Mouse Genome Informatics) knockout mouse that lacks both neutrophils and macrophages shows slightly enhanced rates of re-epithelialisation, again indicating that inflammatory cells release signals that are somewhat inhibitory to repair, but are not themselves essential for healing . …”
mentioning
confidence: 99%